The Effectiveness of Leadership Skills Development Program for University Students / Üniversite Öğrencilerine Yönelik Liderlik Becerileri Geliştirme Programının Etkililiği - Cansoy, Ramazan (Journal of History Culture and Art Research, 2017)
Abstract The aim of this study was to examine the effectiveness of a leadership skills education program for higher education students. In this program, education was provided to improve the desire for struggle and goal setting, communication skills, group skills, problem-solving skills, decision-making skills, responsibility awareness, trusting and trustworthiness awareness, leadership awareness and emotional awareness within the framework of leadership skills. The study group of the research consists of final-year students with the average age of 23.8 years studying at the Faculty of Economics of Karabük University in the 2016-2017 academic year. The data of the study were collected with the “Youth leadership characteristics scale”, “Emotional self-awareness scale” and “Awareness of leader and leadership scale”. The retrospective pretest-posttest experimental model was used in the study. The differentiation levels of the pretest and posttest scores of the students included in the education program were examined with the Wilcoxon signed-rank test. It was observed at the end of the study that the desire for struggle and goal setting, communication skills, group skills, problem-solving skills, decision-making skills, responsibility awareness, trusting and trustworthiness awareness, leadership awareness and emotional awareness levels of the students who participated in the education program significantly increased from a moderately sufficient level to a quite sufficient level. It was indicated that the applied leadership skills education program was effective. Öz Bu araştırmanın amacı, yükseköğretim öğrencilerine dönük olarak geliştirilen bir liderlik becerileri eğitimi programının etkililiğinin incelenmesidir. Bu programda liderlik becerileri çerçevesinde mücadele isteği ve hedef koyma, iletişim becerileri, grup becerileri, problem çözme becerileri, karar verme becerileri, sorumluluk farkındalığı, güven duyma ve güvenilir olma farkındalığı, liderlik farkındalığı ve duygusal farkındalığı geliştirmeye yönelik bir eğitim verilmiştir. Araştırmanın çalışma grubunu 2016-2017 yılında Karabük Üniversitesi’ndeki ortalama yaşı 23.8 olan iktisat fakültesi son sınıf öğrencileri oluşturmaktadır. Araştırmanın verileri “Gençlik Liderlik Özellikleri Ölçeği”, “Duygusal Benlik Bilinci Ölçeği” ve “Lider ve Liderlik Hakkinda Farkindalik Ölçeği” ile toplanmıştır. Çalışmada geçmişe dayalı öntest-son test deneysel modeli kullanılmıştır. Eğitim programında yer alan öğrencilerin öntest ve sontest puanlarının farklılaşma düzeyleri Wilcoxon işaretli sıralar testi ile sınanmıştır. Araştırma sonunda eğitim programına katılan öğrencilerde mücadele isteği ve hedef koyma, iletişim becerileri, grup becerileri, problem çözme becerileri, karar verme becerileri, sorumluluk farkındalığı, güven duyma ve güvenilir olma farkındalığı, liderlik farkındalığı ve duygusal farkındalık düzeylerinin orta derecede yeterli düzeyden oldukça yeterli düzeye anlamlı bir şekilde yükseldiği görülmüştür. Uygulanan liderlik becerileri eğitimi programının etkili olduğu ortaya konulmuştur.